Green Bay Packers - Hunter, Tony (2020)
This title examines the history of the Green Bay Packers, telling the story of the franchise and its top players, greatest games, and most thrilling moments. This book includes informative sidebars, high-energy photos, a timeline, a team file, and a glossary.
Includes bibliographical references (page 47) and index.
Ages 8-11
Keywords: Green Bay Packers (Football team) -- History -- Juvenile literature